An x-band continuous wave saturation recovery electron paramagnetic resonance spectrometer based on an arbitrary waveform generator - McPeak, Joseph E. (Rev Sci Instrum, 2019)
An X-band (ca. 9-10 GHz) continuous wave saturation recovery spectrometer to measure electron spin-lattice relaxation (T(1)) was designed around an arbitrary waveform generator (AWG). The AWG is the microwave source and is used for timing of microwave pulses, generation of control signals, and digitizer triggering. Use of the AWG substantially simplifies the hardware in the bridge relative to that in conventional spectrometers and decreases the footprint. The bridge includes selectable paths with different power amplifications to permit experiments requiring hundreds of milliwatts to fractions of nanowatts for the pump and observe periods. The signal is detected with either a single or quadrature-output double balanced mixer. The system can operate with reflection or crossed-loop resonators. The source noise from the AWG was decreased by addition of a Wenzel high-stability clock. The source is sufficiently stable that automatic frequency control is not needed. The spectrometer was tested with samples that contained 1 × 10(15) to 8 × 10(17) spins and have T(1) between a few hundred ns and hundreds of μs. Excellent signal-to-noise ratio was obtained with acquisition times of 2–90 s. Signal-to-noise performance is similar to that of a conventional saturation recovery spectrometer with a solid-state source. The stability and data reproducibility are better than with conventional sources. With replacement of frequency-sensitive components, this spectrometer can be used to perform saturation recovery measurements at any frequency within the range of the AWG.